2014
DOI: 10.5937/ffr1401011k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Artemisia absinthium essential oil on antioxidative systems of broiler's liver

Abstract: The effect of Artemisia absinthium essential oil (AAEO) on enzymatic activity of superoxide-dismutase (SOD), glutathione-peroxidase (GSHPx), glutathione-reductase (GR), peroxidase (POD), xantine-oxidase (XOD) and non-enzymatic (content of lipid peroxides (LPx) and gluthathione (GSH)) antioxidative status of broilers infected with mixture of oocysts of Eimeria tenella, Eimeria mitis and Eimeria necatrix in comparison to coccidiostat salinomycin was investigated. The in vivo investigation were carried out on 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Moreover, medical herbs are widely being used in different studies to treat cases of parasitism in ruminants, and enviable success has been achieved in this direction against a variety of parasites. Positive results concerning oocyst reduction were recorded in the research of KOSTADINOVIĆ et al (2014), who reported a significant decrease in the fecal oocyst count obtained from chickens which were preventively treated with wormwood in a concentration of 3 g/kg, and subsequently infected with Eimeria spp. In research by the same authors, the reduction of the fecal oocyst count in broiler chickens fed with the addition of wormwood was about 20% compared to the positive control.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, medical herbs are widely being used in different studies to treat cases of parasitism in ruminants, and enviable success has been achieved in this direction against a variety of parasites. Positive results concerning oocyst reduction were recorded in the research of KOSTADINOVIĆ et al (2014), who reported a significant decrease in the fecal oocyst count obtained from chickens which were preventively treated with wormwood in a concentration of 3 g/kg, and subsequently infected with Eimeria spp. In research by the same authors, the reduction of the fecal oocyst count in broiler chickens fed with the addition of wormwood was about 20% compared to the positive control.…”
Section: Discussionmentioning
confidence: 96%
“…Botanicals are commonly used as a topical antiseptic and antibacterial because of its distinguishing antimicrobial features. They reduce inflammation and may be effective in fungal infection treatments (Kostadinović et al, 2016).…”
Section: Characteristics Of Botanicals and Essential Oilsmentioning
confidence: 99%
“…Many plants are used as natural preservatives and medicinal plants, herbs, species and essential oils are the most widely used (Kostadinović et al, 2016;Puvača et al, 2016;Popović et al, 2018). Moreover, the natural preservatives are often used in animal's diet.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of total sialic acid (TSA) is indicated to be a valuable marker for the diagnosis and prognosis of inflammatory diseases (Uzlu et al, 2010;Deveci et al, 2017). As a response to an inflammatory stimulus, free radicals or reactive oxygen species (ROS) are released from dendritic cells, neutrophils, and macrophages (Kostadinović et al, 2016).The produced ROS should be sustained in balance with the antioxidant system in the cell. An increase in ROS levels in cells can cause oxidative stress, which has an important role in the pathophysiology of diseases (Kara et al, 2016;Kükürt et al, 2020;Kostadinović and Lević, 2018. Paraoxonase enzyme activity (PON1)is an antioxidant enzyme found in the serum, liver, kidney, and intestine (Kuru et al, 2020).…”
Section: Introductionmentioning
confidence: 99%